The Dimensions of Spirituality Inventory - Wildman, Wesley J. (Archive for the psychology of religion, 2024)
The Dimensions of Spirituality Inventory (DSI) is a 50-item quantitative assessment of spirituality. Whereas “spirituality” has seemed to some to be too vague for research purposes, the DSI follows earlier qualitative research in showing that usage of the word points to an intelligible conceptual structure. Instead of defining spirituality and then operationalizing it, as most extant instruments do, the DSI defines and operationalizes 21 relatively uncontroversial elemental components of spirituality, so the overall interpretation of spirituality can only emerge after factor analysis. Just as an alphabet flexibly expresses words and sentences, so the 21 DSI dimensions permit the discovery of latent constructs corresponding to cultural packages of spirituality at the present time. The DSI avoids culturally parochial formulations of items, thanks to intense multidisciplinary engagement among social scientists, scholars of religion, and psychologists of religion, and thus is suitable for cross-cultural application. This paper reports on a study based on a participant pool recruited for ExploringMyReligion.org, in part from Prolific (N = 820, after culling unreliable responses). The DSI is interpreted and validated in relation to several other relevant measures, and the factor analysis is strongly resonant with prior qualitative studies. The psychometric properties of the DSI make it usable as an overall spirituality scale as well as a sensitive inventory of types and configurations of spirituality.